OUTCOMES OF TOTAL PROCTOCOLECTOMY (TPC) WITH ILEAL POUCH ANAL ANASTOMOSIS (IPAA). (22nd January 2022) - Petrov, Jessica; Al-Bawardy, Badr; Gaidos, Jill; Proctor, Deborah
Abstract: BACKGROUND: Total proctocolectomy (TPC) followed by ileal pouch anal anastomosis (IPAA) is the surgery of choice for eligible ulcerative colitis patients who are refractory to medical therapy or develop complications such as adenocarcinoma or dysplasia. Although associated with excellent quality of life, IPAA can lead to complications including chronic antibiotic-refractory pouchitis, anatomical complications, and development of Crohn's disease. These outcomes remain a clinical challenge. The aim of this study was to evaluate the rate of complications and their treatment following TPC with IPAA to assess for predictors of adverse postoperative outcomes. METHODS: This was a single center, retrospective study from January 1, 2010 to December 31, 2020. We included patients who underwent TPC with IPAA and reported at least one episode of pouchitis, some of whom also had additional complications. Chronic pouchitis was defined as recurrent episodes of biopsy-proven inflammation or as reported in the patient record based on clinical presentation and responsiveness to treatment. Crohn's disease of the pouch was defined as pre-pouch ileitis or development of a fistula more than 6 months post-operatively. Data is presented as number of cases and proportions. RESULTS: A total of 44 subjects who underwent IPAA (52% female, mean age 46.4 ± 11.3 years) were included. The rate of acute pouchitis was 9%, the rate of chronic pouchitis was 75%. In the chronic pouchitis group, 45% were antibiotic-dependent and 7% were antibiotic-refractory. We found that 70% of subjects required the initiation of medical therapy to treat symptoms of pouchitis, with the majority requiring chronic antibiotics (73%) (Table). A total of 10 subjects (23%) required biologics and 10 subjects (23%) required chronic steroid therapy. Anatomic complications were noted in 23 subjects (52%), the most common being abscess/fistula formation (30%), followed by stricture formation (27%). Anatomic complications appeared more likely to occur when more time had elapsed since the original surgery. 10 subjects (23%) needed repeat surgery and 9 subjects (20%) developed Crohn's disease of the pouch. CONCLUSIONS: In our cohort, we found that nearly two thirds of subjects required medical therapy to treat pouchitis following IPAA including 25% requiring treatment biologic/immunosuppressant therapy. In addition, one quarter required repeat surgery for treatment of complications. Limitations of this study include a tertiary patient population and small sample size. We found a lack of standardized characterization of pouchitis with respect to symptoms and lab abnormalities. In future work, we plan to use this data to develop a prospective, multi-center study to establish a standardized database of patients who underwent IPAA. This will help better understand factors that influence outcomes and guide management.